Development of Multispecies Recombinant Nucleoprotein-Based Indirect ELISA for High-Throughput Screening of Crimean-Congo Hemorrhagic Fever Virus-Specific Antibodies - Shrivastava, Neha; Shrivastava, Ambuj; Ninawe, Sandeep M.; Sharma, Shashi; Kumar, Jyoti S.; Alam, Syed Imteyaz; Kanani, Amit; Sharma, Sushil Kumar; Dash, Paban Kumar (Frontiers in Microbiology, 2019)
Crimean-Congo hemorrhagic fever (CCHF) is a re-emerging zoonotic viral disease prevalent in many parts of Asia, Europe, and Africa. The causative agent, Crimean-Congo hemorrhagic fever orthonairovirus (CCHFV), is transmitted through hard ticks. Tick vectors especially belonging to the Hyalomma species serve as the reservoir and amplifying host. The vertebrate animals including sheep, goat, and bovine act as a short-lasting bridge linking the virus and ticks. CCHFV causes fatal hemorrhagic fever in humans. Humans are usually infected with CCHFV either through the bite of infected ticks or by close contact with infected animals. Immunological assays, primarily enzyme-linked immunosorbent assay (ELISA) using whole viral antigen, are widely used for serosurveillance in animals. However, the whole virus antigen poses a high biohazard risk and can only be produced in biosafety level 4 laboratories. The present study focuses on the development and evaluation of safe, sensitive, and specific IgG indirect enzyme-linked immunosorbent assay (iELISA) using recombinant nucleoprotein (NP) of CCHF virus as an antigen. The codon-optimized NP gene sequence was synthesized, cloned, and expressed in pET28a+ vector. The recombinant NP was purified to homogeneity by affinity chromatography and characterized through Western blot and MALDI-TOF/MS analysis. The characterized protein was used to develop an indirect IgG microplate ELISA using a panel of animal sera. The in-house ELISA was comparatively evaluated vis-à-vis a commercially available ELISA kit (Vector-Best, Russia) with 76 suspected samples that revealed a concordance of 90% with a sensitivity and specificity of 79.4 and 100%, respectively. The precision analysis revealed that the assay is robust and reproducible in different sets of conditions. Further, the assay was used for serosurveillance in ruminants from different regions of India that revealed 18% seropositivity in ruminants, indicating continued circulation of virus in the region. The findings suggest that the developed IgG iELISA employing recombinant NP is a safe and valuable tool for scalable high-throughput screening of CCHFV-specific antibodies in multiple species.